'Predistribution', property-owning democracy and land value taxation. (February 2016) - Kerr, Gavin
The term 'predistribution' draws attention to the need for policies and institutions that are designed to improve the position of the least advantaged members of society by generating a fairer distribution of opportunities and benefits from the operation of the free market system, with less reliance on redistributive tax-and-transfer mechanisms. Although the idea of progressive predistribution has only recently begun to attract the attention of politicians and commentators in the mainstream media, there is an older and more philosophically grounded predistributive approach that goes back to the idea of the property-owning democracy (POD) proposed by Economist James Meade and further developed by liberal political philosopher John Rawls. In this article, I argue that neither the Meadeian/Rawlsian POD model, nor the more recent analysis of the idea of progressive predistribution, provide a clear and convincing account of the distinction between predistributive and redistributive mechanisms. I then argue that a more promising account of this distinction is provided by the idea of the socialization of economic rent through taxation of the rental value of land, and that there are good reasons to think that a shift in the burden of taxation away from production and employment and on to the rental value of land might turn out to be both more genuinely predistributive and more effectively progressive than other possible predistributive mechanisms that have recently been proposed, most notably the aggressive taxation of private inheritances as a means to broaden the distribution of privately owned capital and productive property.